Correlation Analysis of Plasma Myeloperoxidase Level With Global Registry of Acute Coronary Events Score and Prognosis in Patients With Acute Non-ST-Segment Elevation Myocardial Infarction - Zhang, Nan; Wang, Jing-Xian; Wu, Xiao-Yuan; Cui, Yan; Zou, Zhong-He; Liu, Yin; Gao, Jing (Frontiers in Medicine, 2022)
Abstract： Background: Myeloperoxidase (MPO) and Global Registry of Acute Coronary Events (GRACE) risk scores were independently used to predict adverse outcomes in patients with acute coronary syndrome (ACS). However, the relationship between MPO level and GRACE score, and whether the combination of MPO and GRACE can better predict major adverse cardiovascular events (MACEs) in patients with acute non-ST-segment elevation myocardial infarction (NSTEMI), has not been previously investigated. Methods: A prospective cohort of 271 consecutive patients with NSTEMI were enrolled in this study. Plasma MPO levels were measured by ELISA. Baseline demographic and clinical information was collected and GRACE scores were calculated at admission. The correlation between MPO and MACEs was evaluated with GRACE score during 1-year follow-up. Results: The results showed that plasma MPO level was correlated with inflammatory indexes (including hs-CRP, leukocyte count, neutrophil count and fibrinogen), NT-proBNP and hsTNT levels (All p values < 0.05), and there was a statistically significant correlation between plasma MPO level and GRACE score (r=0.22, p< 0.001). Kaplan-meier curves showed that patients with higher MPO levels had lower event-free survival (Log-rank P < 0.001). Multivariate COX model showed that MPO was an independent risk factor for 1-year MACEs in NSTEMI patients (HR:3.85,95%CI:1.4-10.6, p=0.009). Subgroup analysis showed that MPO was a strong prognostic biomarker, and its prognostic value was more significant in patients with age > 65 years and NT-proBNP level > 1000pg/ml. For high-risk patients with GRACE scores, a higher level of MPO has a higher prognostic value. Conclusions: Elevated plasma MPO levels are associated with high inflammatory status and GRACE scores in NSTEMI patients. For high-risk patients with GRACE scores, higher MPO levels were more predictive of future MACEs. Key words: myeloperoxidase, NSTEMI, GRACE score, MACEs, prognosis.